Mirrors of Salt Proceedings of the First International Congress on the Anthropology of Salt : 20-24 August 2015, 'Al. I. Cuza' University, Iași, Romania - Alexianu, Marius; Curcă, Roxana-Gabriela; Weller, Olivier; Dumas, Ashley A. (2023)
Mirrors of Salt publishes the proceedings of the First International Congress on the Anthropology of Salt, which took place at the Alexandru Ioan Cuza University in Iasi (Romania). The impact of salt on the development of human communities, from the Neolithic to the present, has generated a huge number of specialized studies. However, scientific research has become so atomized that the primordial importance of the mineral has been lost, creating a need for a holistic, comprehensive vision of the dimensions generated by salt. This can only be achieved through anthropology. The anthropology of salt encompasses the entirety of human behavior, i.e. cognitive, spiritual, pragmatic, and social reactions to salt, and provides a holistic view of its role in the evolution of human communities. The anthropology of salt thus brings salt studies from an ancillary position to an autonomous discipline. The papers in this volume are organized into six sections: theory, archaeology, history, ethnography/ ethnoarchaeology/ethnohistory, linguistics, and literature. Topics include salt in Greek and Roman antiquity, as well as from Cameroon, Georgia, Ireland, Italy, Mexico, Moldova, Mongolia, Nigeria, Peru, Romania, Spain, Sudan, Syria, Ukraine, the USA and Venezuela. The congress was organized within the project The Ethnoarchaeology of the Salt Springs and Salt Mountains from the Extra-Carpathian Areas of Romania, financed by the Government of Romania (CNCS - UEFISCDI) (2011-2016). Its theoretical novelty and geographical range render Mirrors of Salt a unique study of the world's most-used non-metallic mineral.